2004
DOI: 10.1007/s00595-004-2774-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Fibril Length and Tissue Ingrowth in the Healing of Expanded Polytetrafluoroethylene Grafts

Abstract: Better endothelial healing of ePTFE vascular grafts is correlated with more cellular and capillary ingrowth, but more cellular and capillary ingrowth is not correlated with longer fibril length or higher air porosity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The ePTFE graft has a characteristic node-fibril lattice structure with an average pore size (inter-nodal distance) of 30 μm for a standard graft, which is believed to affect the rate of development of the neointima and endothelialization, which protect against infection [12]. The portion of the graft that migrated into the intestine allows formation of biofilm by the intestinal microbes, and this has been assessed by quantitative cultures and microscopy techniques [13].…”
Section: Discussionmentioning
confidence: 99%
“…The ePTFE graft has a characteristic node-fibril lattice structure with an average pore size (inter-nodal distance) of 30 μm for a standard graft, which is believed to affect the rate of development of the neointima and endothelialization, which protect against infection [12]. The portion of the graft that migrated into the intestine allows formation of biofilm by the intestinal microbes, and this has been assessed by quantitative cultures and microscopy techniques [13].…”
Section: Discussionmentioning
confidence: 99%
“…15 We used 60-µm ePTFE vascular grafts because several laboratories, including ours, found that endothelial healing was better in 60-µm ePTFE vascular grafts than in 30-or 90-µm vascular grafts. 5,9 Transmural tissue ingrowth was most evident in 60-µm grafts, then in 90-µm grafts, and least in 30-µm grafts. 9 Covalent bonding of fibronectin was prepared as described previously.…”
Section: Graft Characteristics and Preparationsmentioning
confidence: 96%
“…5,9 Transmural tissue ingrowth was most evident in 60-µm grafts, then in 90-µm grafts, and least in 30-µm grafts. 9 Covalent bonding of fibronectin was prepared as described previously. 10 The grafts were treated with a mixed solution of methyl lithium and hexamethyl phosphoric amide (Aldrich Chemicals, Milwaukee, WI, USA) in argon gas at 0°C for 30 min, leaving the surface defluorinized.…”
Section: Graft Characteristics and Preparationsmentioning
confidence: 96%
See 1 more Smart Citation
“…3 Pore size can affect the rate of development of the neointima and endothelialization, which is believed to protect against infection. 4 Graft infections can originate either from bacterial colonization of the external surface or from endovascular seeding of the internal surface, but it is unknown if bacteria can translocate from one surface of these porous grafts to another. This question merits assessment because it is critical for understanding the pathogenesis of graft infections.…”
Section: Introductionmentioning
confidence: 99%